Which immigrants are most innovative and entrepreneurial? Distinctions by entry visa - Jennifer Hunt (Institute for the Study of Labor (IZA), 2010)
Using the 2003 National Survey of College Graduates, I examine how immigrants perform relative to natives in activities likely to increase U.S. productivity, according to the type of visa on which they first entered the United States. Immigrants who first entered on a student/trainee visa or a temporary work visa have a large advantage over natives in wages, patenting, commercializing or licensing patents, and publishing. In general, this advantage is explained by immigrants' higher education and field of study, but this is not the case for publishing, and immigrants are more likely to start companies than natives with similar education. Immigrants without U.S. education and who arrived at older ages suffer a wage handicap, which offsets savings to the United States from their having completed more education abroad. Immigrants who entered with legal permanent residence do not outperform natives for any of the outcomes considered.
Keywords: J61; J24; 330; Immigration; innovation; entrepreneurship; visa type; wages; Einwanderung; Qualifikation; Bildungsniveau; Einkommen; Selbstständige; USA